2023
DOI: 10.1039/d3ra06226k
|View full text |Cite
|
Sign up to set email alerts
|

A numerical procedure for understanding the self-absorption effects in laser induced breakdown spectroscopy

Lekha Mary John,
K. K. Anoop

Abstract: Self-absorption (SA) of analytical plasmas is studied by simulating optically thick emission spectra. The study found that SA decreases at higher plasma temperatures but increases with longer optical path lengths and higher analyte concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Aguilera et al 120 found that the self-absorption of non-resonant lines with increasing delay time, and this tendency does not diminish until a specific value. However, it is noteworthy that a simulation method proposed by John et al 123 revealed that resonant lines exhibit stronger selfabsorption compared to non-resonant lines.…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…Aguilera et al 120 found that the self-absorption of non-resonant lines with increasing delay time, and this tendency does not diminish until a specific value. However, it is noteworthy that a simulation method proposed by John et al 123 revealed that resonant lines exhibit stronger selfabsorption compared to non-resonant lines.…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…Dependence of the self-absorption coefficient on the plasma temperature, optical path length and element concentration in a sample was investigated by John et al , 97 using a numerical procedure to simulate optically thick emission spectra. Results indicated that self-absorption decreases with increased plasma temperature, whereas it increases with increasing optical path length and analyte concentration.…”
Section: Laser-based Atomic Spectrometrymentioning
confidence: 99%
“…Recently, our team published a study simulating optical emission spectra under typical LIBS conditions to simulate neutral and singly ionized species [24]. Simulation of optical emission spectra (OES) at typical LPP conditions is a convenient tool for understanding the characteristic emission of lines of multielement samples in LIBS experiments [25,26]. The input parameters for the simulation are electron number density, plasma temperature, and percentage composition (atomic number fraction) of the constituent elements.…”
Section: Simulations Of Optical Emission Spectramentioning
confidence: 99%